Habenaria osmastonii (Orchidaceae), a new terrestrial orchid from the Andaman Islands, India - Karthigeyan, K.; Maina, V.; Sumathi, R.; Jayanthi, J.; Jalal, J.s. (Phytotaxa, 2014)
Habenaria osmastonii, a new species of terrestrial orchid is described from Rutland Island of the Andaman Islands, India. This species differs from H. richardiana by having radical leaves, fewer and smaller flowers, shallowly denticulate, falcate lip side lobes and a lip midlobe slightly longer than the side lobes. A detailed description, illustrations and photographs are provided.